Imiquimod-induced psoriasis-like skin inflammation is suppressed by BET bromodomain inhibitor in mice through RORC/IL-17A pathway modulation. (September 2015) - Nadeem, Ahmed; Al-Harbi, Naif O.; Al-Harbi, Mohamed M.; El-Sherbeeny, Ahmed M.; Ahmad, Sheikh F.; Siddiqui, Nahid; Ansari, Mushtaq A.; Zoheir, Khairy M.A.; Attia, Sabry M.; Al-Hosaini, Khaled A.; Al-Sharary, Shakir D.
Graphical abstract: Abstract: Psoriasis is one of the most common skin disorders characterized by erythematous plaques that result from hyperproliferative keratinocytes and infiltration of inflammatory leukocytes into dermis and epidermis. Recent studies suggest that IL-23/IL-17A/IL-22 cytokine axis plays an important role in the pathogenesis of psoriasis. The small molecule bromodomain and extraterminal domain (BET) inhibitors, that disrupt interaction of BET proteins with acetylated histones have recently demonstrated efficacy in various models of inflammation through suppression of several pathways, one of them being synthesis of IL-17A/IL-22 which primarily depends on transcription factor, retinoic acid receptor-related orphan receptor C (RORC). However, the efficacy and mechanistic aspect of a BET inhibitor in mouse model of skin inflammation has not been explored previously. Therefore, this study investigated the role of BET inhibitor, JQ-1 in mouse model of psoriasis-like inflammation. Mice were topically applied imiquimod (IMQ) to develop psoriasis-like inflammation on the shaved back and ear followed by assessment of skin inflammation (myeloperoxidase activity, ear thickness, and histopathology), RORC and its signature cytokines (IL-17A/IL-22). JQ-1 suppressed IMQ-induced skin inflammation as reflected by a decrease in ear thickness/myeloperoxidase activity, and RORC/IL-17A/IL-22 expression. Additionally, a RORα/γ agonist SR1078 was utilized to investigate the role of RORC in BET-mediated skin inflammation. SR1078 reversed the protective effect of JQ-1 on skin inflammation at both histological and molecular levels in the IMQ model. The current study suggests that BET bromodomains are involved in psoriasis-like inflammation through induction of RORC/IL-17A pathway. Therefore, inhibition of BET bromodomains may provide a new therapy against skin inflammation.